Injury Assistance Ankle on NTB Football Players - Soemardiawan, Soemardiawan; Yundarwati, Susi; Hariyanto, Fitri Anggraini; Marzuki, Ismail (Abdi Masyarakat, 2024)
Based on the situation analysis, In the 2023 NTB ASPROV League 3, all medical teams of the league recorded ankle injuries experienced by 55% of the total number of soccer athlete injuries. The purpose of the study was to realize effective and efficient ankle injury assistance for NTB soccer players in preventing ankle injuries. The method used is the solution method, namely by holding socialization, training, assistance, and evaluation of the analysis of ankle injury assistance for NTB soccer players which is good according to the branch of the soccer sport. The sustainability of the program from this community service activity will later produce a chronic post-ankle injury guideline module to improve the performance of soccer athletes in the NTB League 3 event, the participants of which are 15 coaches from each NTB League 3 club. Increasing the competence of coaches in this assistance process, the success of achieving athlete achievement depends on the coach. In the community service activity, the assistance for ankle injuries in NTB soccer players was able to handle ankle injuries as a reference material in formulating athlete training programs after ankle injuries so that it could improve athlete achievement in the field of soccer. The positive response of the coaches to the implementation of community service is very good, so that the coaches can implement the material obtained from the training process. The results of this study so that the assistance of ankle injuries to NTB Football players is realized effectively and efficiently in preventing ankle injuries